PENGARUH VIRAL MARKETING DAN KEPERCAYAAN PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI MEDIA ONLINE INSTAGRAM (STUDI KASUS PADA KARYAWAN PT. SURYAGITA NUSARAYA DI JAKARTA) - Aminah Nurul Jannah; Widiyono Widiyono (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to determine the viral marketing effects and customer trust on purchasing decisions through sosial media Instagram at PT Suryagita Nusaraya. The independent variables are viral marketing and customer trust affect the purchase decision as the dependent variable.This research used is a quantitative method. The populations in this study are PT Suryagita Nusaraya Jakarta employees. Sampling technique using non-probability sampling technique that is accidental sampling and sample number 89 respondents. This research is a description with survey method. All data are processed by multiple linear regression analysis using SPSS version 21.0 application.The results of this research indicate that viral marketing and customer trust have an influence on purchasing decisions. This can be seen from the results of the F test obtained that the calculated F count is greater than F table (35,430> 3,09), and the probability value Sig. is 0,000 <0,05, the conclution are Ho is rejected and Ha is accepted. That means the viral marketing (X1) and customer trust (X2) together (simultaneous) have a positive and significant effect on purchasing decisions (Y).The determination coefficient result (R2) is viral marketing and customer trust affects purchasing decisions by 45.2%. The remaining 54.8% is influenced by other variables not examined in this model or equation.